Transcarga: Plataforma WEB para el transporte de carga independiente en Colombia. (2018)
The transport of terrestrial independent load is a basic activity for the increase of the productivity and the economic development in Colombia. It is necessary that the independent carriers possess the technological necessary tools to promote his possibilities of market. The design of a web applicative arises as a technological viable alternative to make the virtual communication possible, for the commercial exchange between the independent carriers and the potential clients.